If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3(0) + -6(0) = 0 Multiply 3 * 0 2x + 0 + -6(0) = 0 Anything times zero is zero. 2x + 0 + -6(0) = 0 Multiply -6 * 0 2x + 0 + 0 = 0 Anything times zero is zero. 2x + 0 + 0 = 0 Reorder the terms: 0 + 0 + 2x = 0 Combine like terms: 0 + 0 = 0 0 + 2x = 0 2x = 0 Solving 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '2'. x = 0 Simplifying x = 0
| (2/x-12)(-5x-5) | | 2x-26=5x+10 | | x^2+4x+11=(2x+3)sqrt(x^2+9) | | f(x)=(x-3)(x+2)(x+5) | | X-3.75=0.6 | | x+19=3x+10 | | 3a+5=2a+10 | | x^2+y^2-10x+8y+41=0 | | 4x^2+4y^2-8x-16y-29=0 | | x-x(0.20)=175 | | x+(x(0.20))=175 | | x+-1(x(0.20))=175 | | x-(x(0.25))=175 | | 2kx^2-4x+k=0 | | S-a= | | 8x^2-y^2-2z^2-32=0 | | 4a+2a+3a=9 | | 23-x-56= | | 1/3/20 | | 3rs-5r+4s-6rs+8r-4s= | | a+b+c=49000 | | 3m+2=10+m | | 17=9+2r-8 | | -12=2f-10-8 | | 3j+(-8)=13 | | 1/3m^2-5/3m=1/3m | | -76=3x-6x+1 | | 9(k-1)=36 | | d-16+5d=14 | | y-(-1)=7/8(x-9) | | 3g+5=26 | | 2n+8=6n |